Patients’ and Residents' Evaluations of Patient Centeredness and Communication Skills of Physicians at Jordan University Hospital - Yasein, Nada; jaber, ruba; Shakhatreh, Farouk; shroukh, wejdan; farah, mohammad (Jordan Medical Journal, 2017)
Objective: The objectives of this study were to evaluate patients’ opinions about patient centerednessand communication skills of the physicians at Jordan. University Hospital, and to evaluate physician’sself-assessments of these skills.Methodology: A cross-sectional study of 418 patient and 94 physicians at Jordan University Hospitaloutpatient clinics was performed using two self-reported questionnaires. Data collected were analyzedusing SPSS Statistics version 17.Results: Only half of the patients surveyed stated that their main problem was discussed by theirphysicians, and only half felt that their physicians understood them. Only 32% mentioned that thephysician discussed their respective roles most of the time.Conclusion: Although a number of patients appeared satisfied with their consultations, a higheremphasis on communication skills and the patient-centered approach is needed. This may be achievedby further research in these areas and training sessions for physicians on the patient-centered approach